Unemployment or Overeducation: Which is a Worse Signal to Employers? - Stijn Baert; Dieter Verhaest (Institute for the Study of Labor (IZA), 2014)
This study aims at estimating the stigma effect of unemployment and overeducation within one framework. To this end, we conduct a field experiment in the Belgian labour market. We send out trios of fictitious male job applications to real vacancies. These applications differ only by the labour market history of the candidates. By monitoring the subsequent reactions from the employer side, we find evidence for a larger stigma effect of unemployment than overeducation. The stigma effect of overeducation is found to occur for permanent contract jobs but not temporary ones.
Keywords: J24; J60; C93; 330; unemployment signalling; overeducation signalling; transitions in youth